Analysis of Six Big Losses on Injection Molding Machines to Improve Production Effectiveness - Tawaqqal, Akbar; Harjian, Muhammad Rivaldi; Aprianto, Romi (Journal Industrial Engineering and Management (JUST-ME), 2025)
This study analyzes the six big losses affecting the effectiveness of injection molding machines to enhance production efficiency in the plastics industry. Utilizing Overall Equipment Effectiveness (OEE) as a key metric, the research measures availability, performance, and quality rates across ten injection molding machines to identify dominant loss factors. Through Pareto analysis and fishbone diagrams, the study pinpoints mold replacement, drool in the nozzle, and color replacement as primary contributors to reduced OEE. Data collected via interviews, observations, and company records reveal that idling, minor stops, and equipment failures account for significant time losses, with specific machines exhibiting OEE values as low as 56%. Recommendations include implementing preventive maintenance, standardizing machine parameters, improving production scheduling, and providing operator training to align with Total Productive Maintenance principles. These strategies aim to minimize downtime and optimize equipment utilization, offering practical solutions for improving productivity and competitiveness in manufacturing.